Occurrence of microsporidia as emerging pathogens in Slovak Roma children and their impact on public health - Halánová, Monika; Valenčáková, Alexandra; Malčeková, Beáta; Kváč, Martin; Sak, Bohumil; Květoňová, Dana; Bálent, Pavol; Čisláková, Lýdia (Annals of agricultural and environmental medicine, 2013)
INTRODUCTION AND OBJECTIVE: Microsporidia are identified as ubiquitous organisms of almost every animal group and are now recognized as emerging opportunistic pathogens of human. The risk factors include immunodeficiency, lack of sanitation, and exposure to contaminated water and infected animals. In Slovakia, the places with an increased risk of infection due to the presence of risk factors and routes of transmission are represented by Roma settlements. Therefore, the aim of this work was to study the occurrence of Encephalitozoon spp. and E. bieneusi in children living in Roma settlements. MATERIALS AND METHODS: Stool samples were examined of 72 clinically healthy children coming from a group of the non-integrated Roma minority for the presence of microsporidia Encephalitozoon spp. and E. bieneusi. Microsporidian spores were detected by standard Rylux D, staining and by PCR and DNA sequencing. RESULTS: Of the total number of 72 stool smears examined, 22 were positive, which represented 30.6%. By the Real Time PCR, E. bieneusi was detected in 3 samples (4.2 %) and E. cuniculi in 19 samples (26.4 %). By comparing the sequences with sequences in the GenBank, E. cuniculi genotype I (Accession No. AJ005581.1) and E. bieneusi genotype A (Accession No. AF101197.1). CONCLUSIONS: Microsporidia, as newly emerging pathogens of humans and animals, are characterised by the production of spores which are environmentally resistant. Diseases caused by them have a cosmopolitan occurrence. Although E. bieneusi and E. cuniculi belong to the most frequently diagnosed species of microsporidia in humans, in Slovakia, this is the first confirmed evidence of E. bieneusi genotype A, as well as E. cuniculi genotype I in humans by the molecular method.
Keywords: Infant; feces; Humans; kojenec; dítě; Encephalitozoon; Child; Female; Communicable Diseases, Emerging; Public Health; encephalitozoonóza; veřejné zdravotnictví; lidé; Slovakia; Slovenská republika; Feces; předškolní dítě; Encephalitozoonosis; objevující se infekční nemoci; ženské pohlaví; Male; Adolescent; mužské pohlaví; Child, Preschool; mladiství